COMMUNITY PARTICIPATION IN THE DEVELOPMENT OF SITU JANGGALA TOURISM IN PANAWUAN VILLAGE, CIGANDAMEKAR DISTRICT, KUNINGAN DISTRICT - Sutarjo, Moh; Yuniarsih, Anih (Politeknik Siber Cerdika Internasional, 2024)
This research aims to determine community participation; to determine factors inhibiting community participation; and efforts to overcome obstacles to community participation in the development of Situ Janggala Tourism in Panawuan Village. The method used in this research is qualitative method. The data collection techniques used are observation, interviews and documentation. The results of this research indicate that community participation in Panawuan Village has not been optimal. Barriers to community participation are low public awareness to participate in the development of Situ Janggala Tourism, lack of funds to support the development process of Situ Janggala Tourism, lack of infrastructure to support community participation in the development of Situ Janggala Tourism and time. These factors mean that the community has not been maximally involved in the development of Situ Janggala Tourism. Efforts are being made to overcome these obstacles by approaching the community through outreach regarding the importance of community participation in the development of Situ Janggala Tourism, managing funds in detail according to needs, providing adequate facilities for mutual cooperation activities in the context of developing Situ Janggala Tourism, and carrying out activities development of Situ Janggala Tourism in turns according to the free time each community has.